Pembrolizumab in a Patient With a Metastatic CASTLE Tumor of the Parotid - Lisa Lorenz; Joscha von Rappard; Walter Arnold; Nicole Mutter; Udo Schirp; Andreas Scherr; Andreas Werner Jehle; Andreas Werner Jehle (Frontiers in Oncology, 2019)
Carcinoma showing thymus-like elements (CASTLE) is a rare tumor, most commonly found in the thyroid gland. Here we report a case of CASTLE tumor localized to the parotid gland, recognized in retrospect after a late manifestation of symptomatic pleural carcinomatosis. The original tumor in the parotid gland was treated by surgery followed by radiotherapy. Ten years later, a metastatic disease with recurrent pleural effusions occurred. Pleural carcinomatosis was strongly positive for CD5, CD117, and p63 as was the original tumor of the parotid, which allowed the diagnosis of a CASTLE tumor. Additionally, the pleural tumor expressed high levels of programmed death ligand 1 (PD-L1), and the patient underwent treatment with the monoclonal PD-L1 inhibitor pembrolizumab achieving a partial remission. To the best of our knowledge, this is the first patient with a metastatic CASTLE tumor treated with a PD-L1 inhibitor.